Isolation of aporphine alkaloid from the leaves of Alseodaphne corneri Kosterm - Khoo Jennie, Hui Chen, Ahmad Kartini, Hasnan Muhammad Hafiz Husna, Mohammad Siti Nor Fadzilah, Awang Khalijah, A. Hadi A. Hamid, Nafiah Mohd Azlan (N/A, 2014)
Isolation of aporphine alkaloid from the leaves of Alseodaphne corneri Kosterm by Khoo Jennie, Hui Chen, Ahmad Kartini, Hasnan Muhammad Hafiz Husna, Mohammad Siti Nor Fadzilah, Awang Khalijah, A. Hadi A. Hamid, Nafiah Mohd Azlan,